أطياف نجيب محفوظ " افراح القبة " إنموذجا (Journal of the College of Basic Education, 2019)
the kings spectrum in (Hamlet) play to be a sample in his narrative experience , and to reveal his view of the age who has "no morals to him"In this research we stand "on the specter of Najib Mahfuz" since it early beginnings which were represented in his view of modernity, and his experience in it , so it was the vision of modernity in the "emancipation of women " , and the defeat of the patariachal system , and self questioning our most important position in this research , and it represent the narrative and cultural spectrum of Mahfuz .